Antibacterial activities of three species of mangrove leaves extract against Staphylococcus aureus and Escherichia coli - Rahmawati, Ayu; Nursyafni, Nursyafni; Herly, Moh. Azhari Herly Azhari; Indriani, Lusi; Lovena, Tri Nova; Khairiah, Kinanti Bahy; Aprilia, Indri (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
The increasing incidence of infections and drug resistance has led scientists to seek approaches towards medicinal plants that are potentially effective against many microorganisms. Therefore, this study was planned to assess the antibacterial activity of 3 mangrove species (Scyphipora hydrophylaceae C.F.Gaertn., Lumnitzera littorea (Jack) Voigt and Avicennia alba Blume) against Staphylococcus aureus and Escherichia coli bacteria. This study used the disc diffusion method to measure the diameter of inhibition at several concentrations of mangrove leaf ethanol extracts, namely 15%, 10%, 5%, 2.5%, 1.25% and 0.625% b/v as well as positive control cefadroxil for bacteria and DMSO as negative control. The test results showed that ethanol extracts of mangosteen leave Scyphipora hydrophylaceae C.F.Gaertn and Lumnitzera littorea (Jack) Voigt had a solid response to Escherichia coli bacteria and moderate potential against S. Aureus bacteria—no antibacterial activity against both test bacteria for Avicennia alba mangrove. This study concludes that Scyphipora hydrophylaceae C.F.Gaertn and Lumnitzera littorea (Jack) Voigt have potent antibacterial activity against Escherichia coli, but Avicennia alba has no antibacterial activity.